Reflecting With Teachers on Research-Based Tools: The ySKILLS Education Toolkit - Susana Batista; Cristina Ponte; Rita Baptista (Media and Communication)
This article focuses on the links between academic research and educational practices, examining how practitioners use, contextualize, and co-construct research findings on digital skills. To explore these issues, firstly we present an education toolkit developed within a European research project and aligned with normative and substantive guidelines for science communication. Aiming to grasp the potentialities and limitations of the toolkit in action, we then explore the perceptions of teachers from two educational settings in Portugal who employed it in their classrooms. Subsequent focus groups evidenced overall positive feedback from teachers, complemented by practical tips to improve the usefulness of the toolkit and adherence to it by teachers and students, thus adding layers of knowledge to the performative dimension of an evidence-based resource and building bridges between the academic and professional worlds.